2011
DOI: 10.1682/jrrd.2010.08.0145
|View full text |Cite
|
Sign up to set email alerts
|

Using multifractal detrended fluctuation analysis to assess sacral skin blood flow oscillations in people with spinal cord injury

Abstract: Abstract-The purpose of this study was to investigate whether the multifractal detrended fluctuation analysis (MDFA) of skin blood flow oscillations (BFO) differed between nondisabled controls and people with spinal cord injury (SCI). The study of skin BFO has shown promise for assessing blood flow control mechanisms and risk for pressure ulcers. We recruited 23 subjects, including 11 people with SCI and 12 nondisabled controls. Thermally induced maximal sacral skin BFO were measured by laser Doppler flowmetry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…spinal cord injury, peripheral neuropathy) on microvascular dysfunction and its influences on the risk for ischemic injury and subsequent pressure ulcers. We also demonstrated that nonlinear properties of skin BFO are associated with vasodilatory function [20, 21]. By assessing the nonlinear property of blood flow oscillations, the clinicians may better understand the effect of various risk factors of pressure ulcer on causing soft tissue ischemia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…spinal cord injury, peripheral neuropathy) on microvascular dysfunction and its influences on the risk for ischemic injury and subsequent pressure ulcers. We also demonstrated that nonlinear properties of skin BFO are associated with vasodilatory function [20, 21]. By assessing the nonlinear property of blood flow oscillations, the clinicians may better understand the effect of various risk factors of pressure ulcer on causing soft tissue ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…The study of skin microcirculation may be used to assess risk for pressure ulcers and effectiveness of preventive intervention [11, 12, 14, 15, 21]. A basic function of skin microcirculation is to regulate blood flow to meet the metabolic demands of local cells and to regulate skin temperature through a dynamic control of vascular resistance and blood flow redistribution [34, 35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An application of MF-DFA may cover many dierent problems in science, just to mention examples in seismology [12,13], cosmology [14], biology [15,16], meteorology [17], medicine [18], epidemiology [19], music [20,21], geophysics [22] and mostly nances [2331].…”
Section: Introductionmentioning
confidence: 99%
“…Skin blood flow has been found to exhibit irregular fluctuations over time [1416]. Griffith [15] suggested that spontaneous contraction and dilation of the vessel wall and the nonlinear rheological properties of blood may contribute to this phenomenon.…”
Section: Introductionmentioning
confidence: 99%